Effects of a preschool intervention on cognitive development among East-African preschool children A flexibly time-coded growth model - Malmberg, L; Mwaura, P; Sylva, K (2011)
The aim of the study is to investigate the effects of the Madrasa Resource Center (MRC), a child-centered intervention program, on East-African (Kenya, Zanzibar, and Uganda) preschool children's cognitive development. Altogether 321 children (153 non-intervention and 168 intervention) participated in a cross-sequential study over three time-points during preschool (mean ages 4.3, 6.0, and 7.1 years). A multilevel model (MLM; time-points nested within children nested within schools), in which time was coded flexibly (i.e., child's age operationalized as months from start of the intervention), showed a beneficial curvilinear effect of the intervention program on children's cognitive gains. A moderation analysis suggested that the effect of observed preschool quality (ECERS) was stronger in the intervention program. The findings are discussed within the context of East-African preschool policy. © 2010 Elsevier Inc.